Hubungan Tingkat Stres, Pengaruh Keluarga, dan Teman Sebaya dengan Status Merokok pada Mahasiswa Laki-Laki UIN Syarif Hidayatullah Jakarta Tahun 2019 - Eva Dwiyanti Lestari; Siti Ahlan Sarmadani; Safira Hani Pratiwi; Novera Nur Fikri; Ahmad Solihin Hafi; Hoirun Nisa (Media Penelitian dan Pengembangan Kesehatan, 2019)
Abstract Smoking is an unhealthy behavior that causes high morbidity and mortality. In Indonesia the prevalence of smokers is still high, and the number of smokers among university students tends to increase. Smoking status among male students of Syarif Hidayatullah State Islamic University (UIN) Jakarta and factors related to smoking status behavior are not yet clearly known. This study was conducted to determine the relationship of stress levels, the influence of family and peers with smoking status on male students of UIN Syarif Hidayatullah Jakarta in 2019. This study used a cross sectional study design to determine the smoking status of male students of UIN Syarif Hidayatullah Jakarta. A purposive sampling technique was used to select 424 male university students. Data analysis was performed using the chi square test and binary logistic regression. The Results is the prevalence of smokers among male students of UIN Jakarta was 42.2%. The results of multivariate analysis showed that family and peers were significantly related to smoking status of students (p-value <0.05), while stress levels were not related. Odds ratio (OR) associated for family influence is 1.9 (95% Confidence Interval (CI): 1.24-2.93) and OR (95% CI) for with peer influence is 13.6 (6.20-29.81). The Conclusion is the prevalence of smokers is still quite high among male students at UIN Syarif Hidayatullah Jakarta. The influence factor of family and peers is related to smoking status of UIN Syarif Hidayatullah Jakarta student. Abstrak Merokok merupakan perilaku tidak sehat yang menyebabkan tingginya angka kesakitan dan kematian. Di Indonesia prevalensi perokok masih tinggi dan jumlah perokok di kalangan mahasiswa cenderung mengalami peningkatan. Status merokok mahasiswa Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta dan faktor yang berhubungan dengan status merokok belum diketahui dengan jelas. Penelitian ini dilakukan untuk mengetahui hubungan tingkat stres, pengaruh keluarga, dan teman sebaya dengan status merokok pada mahasiswa UIN Syarif Hidayatullah Jakarta Tahun 2019. Penelitian ini menggunakan desain studi cross sectional untuk mengetahui status merokok mahasiswa laki-laki UIN Syarif Hidayatullah Jakarta. Teknik purposive sampling dilakukan untuk memilih 424 responden. Analisis data dilakukan dengan menggunakan uji chi square dan binary logistic regression. Hasil menunjukan prevalensi perokok pada mahasiswa laki-laki di UIN Syarif Hidayatullah Jakarta sebesar 42,2%. Hasil analisis multivariat menunjukkan bahwa keluarga dan teman sebaya berhubungan bermakna dengan status merokok mahasiswa (p-value <0,05), sedangkan level stres tidak berhubungan. Odds ratio (OR) untuk pengaruh keluarga sebesar 1,9 (95% Confidence Interval (CI): 1,24-2,93) dan OR (95% CI) untuk pengaruh teman sebaya sebesar 13,6 (6.20-29.81). Kesimpulannya adalah prevalensi perokok masih cukup tinggi pada mahasiswa laki-laki di UIN Syarif Hidayatullah Jakarta. Faktor pengaruh keluarga dan teman sebaya berhubungan dengan status merokok mahasiswa UIN Syarif Hidayatullah Jakarta.